High-hardness crack-free flux-cored wire and preparation method thereof

By reasonably preparing the pharmaceutical core components in the flux-core welding wire and controlling the powder filling rate, the problem of cracks and breakages in the flux-core welding wire is solved, and the welding effect of high hardness, no cracks, good wear resistance and corrosion resistance is achieved.

CN119635072AActive Publication Date: 2025-03-18ZHUHAI HONGDE SURFACE TECH CO LTD

Patent Information

Application Number
CN202411956074.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-03-18
Estimated Expiration
2044-12-28

Smart Images

  • Figure CN119635072A_ABST
    Figure CN119635072A_ABST
Patent Text Reader

Abstract

The invention provides a high-hardness crack-free flux-cored wire and a preparation method thereof.The flux-cored wire comprises an outer skin and a flux core, and the flux core comprises, by weight, 5.6-8.6 parts of boron carbide; 3.1 to 4.6 parts of 75% silicon iron; 0.6 to 1.6 parts of electrolytic manganese; 0.3 to 1.2 parts of 80% ferrovanadium; 0.3 to 1.0 part of nickel powder; 67.5 to 94.5 parts of 68% high carbon ferro-chrome; 6 to 6.5 parts of iron powder; the preparation method of the flux-cored wire comprises the steps that boron carbide, 75% ferrosilicon, electrolytic manganese, 80% ferrovanadium, nickel powder, 68% high-carbon ferrochrome and iron powder are sequentially added into a drying machine according to the formula to be dried for 2-3 h, then a three-dimensional motion mixing machine is adopted for fully and evenly mixing, and then the mixture is put into a heat preservation box to be subjected to heat preservation for use; the outer skin is placed on a forming machine, and an outer skin steel belt is rolled into a U-shaped groove through the forming machine; flux core powder is added into the U-shaped groove, a forming machine rolls and closes the U-shaped groove and draws the U-shaped groove, and the flux-cored wire is obtained; the flux-cored wire has the advantages of being high in hardness, free of cracks, resistant to high temperature and corrosion, low in production cost and beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material processing and welding materials, and in particular relates to a high-hardness crack-free flux-cored welding wire and a preparation method thereof. Background Art

[0002] Flux-cored welding wire is also called powder-cored welding wire or tubular welding wire. It is divided into two categories: gas-entrained and non-gas-entrained. The surface of flux-cored welding wire is the same as solid welding wire, and is made of low-carbon steel or low-alloy steel with good plasticity.

[0003] The commonly used flux-cored welding wire is prone to cracking and breaking during surfacing, which affects the use of flux-cored welding wire.

[0004] Therefore, it is necessary to provide a crack-free, high-hardness flux-cored welding wire and a preparation method thereof. Summary of the invention

[0005] One object of the present invention is to provide a high-hardness, crack-free flux-cored welding wire, and another object of the present invention is to provide a method for preparing the high-hardness, crack-free flux-cored welding wire.

[0006] To achieve the first purpose of the present invention, the following technical solution is adopted:

[0007] A high-hardness, crack-free flux-cored welding wire, the flux-cored welding wire comprising an outer sheath and a flux core filled in the outer sheath, the flux core comprising the following components by weight:

[0008] Boron carbide 5.6-8.6 parts; 75% ferrosilicon 3.1-4.6 parts; electrolytic manganese 0.6-1.6 parts; 80% ferrovanadium 0.3-1.2 parts; nickel powder 0.3-1.0 parts; 68% high carbon ferrochrome 67.5-94.5 parts; iron powder 5.7-6.7 parts;

[0009] Wherein, the filling rate of the medicine powder in the medicine core is 30-45%.

[0010] Preferably, the drug core comprises the following components in parts by weight:

[0011] 7.1 parts of boron carbide; 3.7 parts of 75% ferrosilicon; 1.0 parts of electrolytic manganese; 0.6 parts of 80% ferrovanadium; 0.5 parts of nickel powder; 81 parts of 68% high carbon ferrochrome; and 6.2 parts of iron powder.

[0012] Preferably, the filling rate of the medicine powder in the medicine core is 45%.

[0013] Preferably, the chemical composition of the deposited metal of the flux core comprises the following components by weight percentage:

[0014] Boron: 1.8-2.8%; Carbon: 1.5-2.5%; Silicon: 1-1.5%; Manganese: 0.3-0.8%; Vanadium: 0.1-0.4%; Nickel: 0.1-0.4%; Chromium: 20-28%, and the balance is iron.

[0015] The present invention will be further described below:

[0016] In the present invention, the flux-cored welding wire needs to be used for surfacing operations. Therefore, there are certain requirements for the physical and chemical properties of the flux-cored welding wire. For example, the flux-cored welding wire is required to have high hardness and no cracks. In addition, the flux-cored welding wire is also required to have high temperature resistance and corrosion resistance. Based on this, the flux-cored welding wire of the present invention is developed.

[0017] In the present invention, each component of the flux core in the flux cored welding wire has a corresponding function, which is as follows:

[0018] Boron carbide has high wear resistance, high hardness and good chemical stability. Boron carbide can improve the hardness and wear resistance of flux-cored welding wire;

[0019] 75% ferrosilicon refers to a ferrosilicon alloy with a silicon content of 75%, in which silicon atoms combine with iron atoms to form silicon-containing ferrite with strong covalent bonds, which not only promotes the formation of ferrite, but also significantly strengthens ferrite. The combination of the two improves the strength, plasticity and toughness of flux-cored welding wire.

[0020] Electrolytic manganese has high strength and hardness, as well as certain plasticity and toughness, which can improve the strength, hardness and toughness of flux-cored welding wire;

[0021] 80% ferrovanadium refers to a ferrovanadium alloy with a vanadium content of 80%. It has good corrosion resistance and can remain stable in harsh chemical environments, which can improve the corrosion resistance of flux-cored welding wires.

[0022] Nickel powder has good corrosion resistance, is not easily oxidized in the air, and is resistant to strong alkali. At the same time, nickel powder also has good plasticity. Therefore, nickel powder can improve the corrosion resistance and plasticity of flux-cored welding wire.

[0023] 68% high carbon ferrochrome refers to a ferrochrome alloy with a chromium content of 68%, which has the characteristics of good chemical stability, wear resistance and high hardness. Therefore, it can improve the wear resistance and hardness of flux-cored welding wire.

[0024] Iron powder can increase the deposition rate in flux-cored welding wire, combining with other metals to form a weld with certain strength and toughness.

[0025] In the present invention, the powder filling rate in the flux core is 30-45%. Under normal circumstances, the filling rate needs to be kept appropriate, otherwise it will affect the performance of the flux-cored welding wire and the stability of the welding process. If the filling rate is too low, the welding wire may not be filled solidly, and powder leakage may occur easily in the subsequent process. In addition, it is easy to be squeezed and flattened by the wire feeding wheel during welding, resulting in uneven wire feeding. At the same time, due to the loose structure of the welding wire, the gas brought into the molten pool increases, which may cause pores in the weld. On the contrary, if the filling rate is too high, it will increase the difficulty of rolling and drawing. In an extreme case, the outer skin cannot wrap the flux core powder, resulting in waste of flux core powder leakage, affecting the rolling process. Therefore, it is necessary to select an appropriate filling rate. In the present invention, after many tests and demonstrations, the preferred filling rate of the flux core is 45%, which can produce a better filling effect, and the flux-cored welding wire obtained by rolling and drawing is in good condition.

[0026] In the present invention, the chemical composition of the deposited metal of the flux core also has corresponding effects, specifically:

[0027] The role of the boron (B) element is to strengthen the matrix and refine the grains, thereby improving the strength, hardness, plasticity and toughness of the flux-cored welding wire;

[0028] The role of carbon (C) element is to strengthen the matrix and generate hard phase, so that the flux-cored welding wire has a phase with high hardness and high melting point;

[0029] The role of silicon (Si) is to strengthen the matrix and stitch the grain boundaries, making the grain boundaries between the grains in the flux-cored welding wire more regular and tight, thereby improving the strength, plasticity and toughness of the flux-cored welding wire;

[0030] The role of manganese (Mn) is to strengthen and toughen the matrix, thereby improving the strength and toughness of the flux-cored wire, absorbing the energy generated by the flux-cored wire during surfacing, and reducing the generation and expansion of cracks;

[0031] The role of vanadium (V) element is to refine the grains and generate dispersed high-hardness non-sharp-angle reinforcement phase, thereby enhancing the strength and hardness of the flux-cored welding wire. Due to the absence of sharp angles, the reinforcement phase can distribute stress more evenly and avoid stress concentration, thereby reducing local damage and crack initiation of the flux-cored welding wire. The reinforcement phase can also form a barrier inside the material to hinder the expansion of existing cracks, thereby improving the fracture toughness of the flux-cored welding wire; furthermore, the reinforcement phase also has good thermal stability and wear resistance, so that the flux-cored welding wire has high wear resistance and temperature resistance;

[0032] The role of nickel (Ni) is to strengthen and toughen the matrix and neutralize the hard phase performance, thereby improving the strength and toughness of the flux-cored wire, and also inhibiting the propagation of cracks, which helps to improve the overall stability and durability of the flux-cored wire;

[0033] The role of chromium (Cr) element is to neutralize and optimize the affinity between the matrix and the reinforcement, reduce the crack tendency, and thus reduce the occurrence of cracks in the flux-cored welding wire.

[0034] To achieve the second purpose of the present invention, the following technical solution is adopted:

[0035] A method for preparing the high-hardness crack-free flux-cored welding wire as described above comprises the following steps:

[0036] S1, boron carbide, 75% ferrosilicon, electrolytic manganese, 80% ferrovanadium, nickel powder, 68% high carbon ferrochrome and iron powder are added to a dryer at a temperature of 180-220°C for 2-3 hours, and then put into a three-dimensional motion mixer at a temperature of 200°C to mix well, and then put into an incubator at a temperature of 140-160°C to keep warm, and the obtained core powder is set aside;

[0037] S2, placing the outer skin on a forming machine, and rolling the outer skin steel strip into a U-shaped groove by the forming machine;

[0038] S3, adding the flux core powder into the U-shaped groove and controlling the powder filling rate in the flux core to be 30-45%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and pulling it to obtain flux cored welding wire.

[0039] Preferably, the temperature of the drying machine is 200°C, and the temperature of the heat preservation box is 150°C.

[0040] Preferably, the outer skin is a low-carbon steel strip. In the present invention, a high-quality low-carbon steel strip is selected as the outer skin of the flux-cored welding wire.

[0041] More preferably, the low carbon steel strip has a thickness of 0.4 mm and a width of 14 mm.

[0042] Preferably, in S3, the welding wire is wiped with anhydrous ethanol before drawing.

[0043] Preferably, the diameter of the flux-cored welding wire obtained by drawing is 2.8 mm.

[0044] Preferably, the steps of the preparation method may further include:

[0045] S4, winding the flux-cored welding wire layer into a disc to obtain a finished product of a high wear-resistant flux-cored welding wire for mold steel.

[0046] Beneficial effects of the present invention:

[0047] The flux-cored welding wire of the present invention has the following properties:

[0048] ① In the present invention, the addition of boron carbide and 68% high carbon ferrochrome makes the flux-cored welding wire have high hardness and wear resistance. The Rockwell hardness HRC of the flux-cored welding wire of the present invention is between 60 and 62;

[0049] ② The manganese and chromium elements provided by electrolytic manganese and 68% high carbon ferrochrome strengthen and toughen the matrix, neutralize and optimize the affinity between the matrix and the reinforcement, reduce the crack tendency, and make the flux-cored welding wire have the characteristics of no crack;

[0050] ③80% vanadium element provided by ferrovanadium refines grains and generates dispersed high-hardness non-sharp-angle reinforcement phase, in which the reinforcement phase has good thermal stability and wear resistance, making the flux-cored welding wire highly wear-resistant and heat-resistant. The relative wear resistance is 2.5-2.8 times that of Cr26 high-chromium cast iron, and the Vickers hardness is maintained at HV at 850℃ 10 Not less than 530;

[0051] ④ The vanadium element provided by 80% ferrovanadium enables the flux-cored welding wire to perform well in molten salt corrosion at 750°C for 48 hours, so that the flux-cored welding wire of the present invention has good corrosion resistance and can remain stable in harsh chemical environments;

[0052] ⑤ The preparation method of the flux-cored welding wire of the present invention is simple and easy to use. It can be directly welded manually or automatically by machine, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a microhardness test diagram of single-layer surfacing of flux-cored welding wire according to Example 1 of the present invention;

[0054] Figure 2 This is a microhardness test diagram of single-layer surfacing of flux-cored welding wire in Example 2 of the present invention. DETAILED DESCRIPTION

[0055] The present invention can be further understood by the specific examples of the present invention given below, but they are not intended to limit the present invention.

[0056] Example 1

[0057] The present embodiment 1 provides a high-hardness crack-free flux-cored welding wire, which includes an outer skin and a flux core filled in the outer skin. The flux core includes the following components by weight: 5.6 parts of boron carbide; 3.1 parts of 75% ferrosilicon; 0.5 parts of electrolytic manganese; 0.3 parts of 80% ferrovanadium; 0.3 parts of nickel powder; 67.5 parts of 68% high-carbon ferrochrome; and 5.7 parts of iron powder.

[0058] The filling rate of the medicine powder in the medicine core is 30%.

[0059] On the above basis, among the above components, the total content of boron is 1.8%, the total content of carbon is 1.5%, the total content of silicon is 1%, the total content of manganese is 0.3%, the total content of vanadium is 0.1%, the total content of nickel is 0.1%, the total content of chromium is 20%, and the total content of iron is 75.2%.

[0060] The preparation method of the high-hardness crack-free flux-cored welding wire of this embodiment 1 is as follows:

[0061] S1, add 5.6 parts of boron carbide, 3.1 parts of 75% ferrosilicon, 0.5 parts of electrolytic manganese, 0.3 parts of 80% ferrovanadium, 0.3 parts of nickel powder, 67.5 parts of 68% high carbon ferrochrome and 6 parts of iron powder in a drying machine at a temperature of 180°C for 2 hours, put them into a three-dimensional motion mixer at a temperature of 200°C and mix them evenly, then put them into an incubator at a temperature of 140°C for insulation, and the obtained core powder is set aside;

[0062] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;

[0063] S3. Add flux core powder to the U-shaped groove and control the powder filling rate in the flux core to 30%. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a welding wire diameter of 2.8 mm to obtain a flux-cored welding wire. Wipe the welding wire with anhydrous ethanol before drawing.

[0064] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of a high wear-resistant flux-cored welding wire for mold steel.

[0065] After observation, the flux-cored welding wire of Example 1 has no cracks.

[0066] The flux-cored welding wire of Example 1 has three layers with a thickness of 10 mm without cracking.

[0067] Metallographic observation Figure 1 As shown, the single-layer cladding hard phase of Example 1 is dispersedly distributed and strengthened, and the microstructure is evenly distributed.

[0068] The flux-cored welding wire of Example 1 has no obvious oxidation and wear after being deposited on the conveying roller at 1200° C. for 90 days.

[0069] Example 2

[0070] This embodiment 2 provides a high-hardness crack-free flux-cored welding wire, which includes an outer skin and a flux core filled in the outer skin. The flux core includes the following components by weight: 7.1 parts of boron carbide; 3.7 parts of 75% ferrosilicon; 1.0 parts of electrolytic manganese; 0.6 parts of 80% ferrovanadium; 0.5 parts of nickel powder; 81 parts of 68% high-carbon ferrochrome; and 6.2 parts of iron powder.

[0071] The filling rate of the medicine powder in the medicine core is 45%.

[0072] On the above basis, among the above components, the total content of boron is 2.3%, the total content of carbon is 2%, the total content of silicon is 1.3%, the total content of manganese is 0.5%, the total content of vanadium is 0.2%, the total content of nickel is 0.2%, the total content of chromium is 24%, and the total content of iron is 69.5%.

[0073] The preparation method of the high hardness crack-free flux-cored welding wire of this embodiment 2 is as follows:

[0074] S1, add 7.1 parts of boron carbide, 3.7 parts of 75% ferrosilicon, 1.0 parts of electrolytic manganese, 0.6 parts of 80% ferrovanadium, 0.5 parts of nickel powder, 81.0 parts of 68% high carbon ferrochrome and 6.2 parts of iron powder in turn, add them to a dryer at a temperature of 200°C for 2.5 hours, put them into a three-dimensional motion mixer at a temperature of 200°C to mix them evenly, then put them into an incubator at a temperature of 150°C to keep them warm, and the obtained core powder is used for standby;

[0075] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;

[0076] S3. Add flux core powder to the U-shaped groove and control the powder filling rate in the flux core to 45%. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a welding wire diameter of 2.8 mm to obtain a flux-cored welding wire. Wipe the welding wire with anhydrous ethanol before drawing.

[0077] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of a high wear-resistant flux-cored welding wire for mold steel.

[0078] After observation, the flux-cored welding wire of Example 2 has no cracks.

[0079] The flux-cored welding wire of Example 2 has three layers with a thickness of 10 mm without cracking.

[0080] Metallographic observation Figure 2 As shown, the single-layer cladding hard phase of Example 2 is dispersedly distributed and strengthened, and the microstructure is evenly distributed.

[0081] The flux-cored welding wire of Example 2 has no obvious oxidation and wear after being deposited on the conveyor roller at 1200° C. for 90 days.

[0082] Example 3

[0083] Embodiment 3 provides a high-hardness crack-free flux-cored welding wire, which includes an outer skin and a flux core filled in the outer skin. The flux core includes the following components by weight: 8.6 parts of boron carbide; 4.6 parts of 75% ferrosilicon; 1.6 parts of electrolytic manganese; 1.2 parts of 80% ferrovanadium; 1.0 part of nickel powder; 94.5 parts of 68% high-carbon ferrochrome; and 6.7 parts of iron powder.

[0084] Among them, the filling rate of medicine powder in the medicine core is 38%.

[0085] On the above basis, among the above components, the total content of boron is 2.8%, the total content of carbon is 2.5%, the total content of silicon is 1.5%, the total content of manganese is 0.8%, the total content of vanadium is 0.4%, the total content of nickel is 0.4%, the total content of chromium is 28%, and the total content of iron is 63.6%.

[0086] The preparation method of the high-hardness crack-free flux-cored welding wire of this embodiment 3 is as follows:

[0087] S1, 8.6 parts of boron carbide, 4.6 parts of 75% ferrosilicon, 1.6 parts of electrolytic manganese, 1.2 parts of 80% ferrovanadium, 1.0 part of nickel powder, 94.5 parts of 68% high carbon ferrochrome and 6.5 parts of iron powder were sequentially added into a drying machine at a temperature of 220°C for 3 hours, and then put into a three-dimensional motion mixer at a temperature of 200°C to mix well, and then put into an incubator at a temperature of 160°C to keep warm, and the obtained core powder was set aside;

[0088] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;

[0089] S3. Add flux core powder to the U-shaped groove and control the powder filling rate in the flux core to be 38%. The forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a diameter of 2.8 mm to obtain a flux-cored welding wire. Wipe the welding wire with anhydrous ethanol before drawing.

[0090] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of a high wear-resistant flux-cored welding wire for mold steel.

[0091] After observation, the flux-cored welding wire of Example 3 has no cracks.

[0092] The flux-cored welding wire of Example 3 has three layers with a thickness of 10 mm without cracking.

[0093] The flux-cored welding wire of Example 3 has no obvious oxidation and wear after being deposited on the conveyor roller at 1200° C. for 90 days.

[0094] Example 4

[0095] Hardness performance test

[0096] According to the test methods in GB / T 230.1-2009 Rockwell hardness test for metal materials and GB / T 4340.1-2009 Vickers hardness test for metal materials, the flux-cored welding wires prepared in Examples 1-3 were subjected to Rockwell hardness performance tests and Vickers hardness performance tests, respectively. The test results are shown in Table 1 and Table 2, respectively.

[0097] Table 1 Rockwell hardness performance test results

[0098] Test Group Example 1 Example 2 Example 3 Rockwell hardness HRC 60.7 61.8 60.3

[0099] Table 3 Vickers hardness performance test results

[0100] Test Group Example 1 Example 2 Example 3 850℃ Vickers hardness HRC 536 551 540

[0101] Example 5

[0102] Wear resistance test

[0103] According to the loose abrasive wear test method of JB / T 7705-1995, the wear resistance of the flux-cored welding wires prepared in Examples 1-3 and the Cr26 high chromium cast iron sold on the market was tested by the rubber wheel method. The test results are shown in Table 3.

[0104] Table 3 Wear resistance test results

[0105] Test Group Initial mass m1 / g Mass after wear m2 / g Wear loss△m / g Example 1 70.323 70.252 0.071 Example 2 70.234 70.159 0.075 Example 3 70.217 70.148 0.069 Cr26 high chromium cast iron 70.223 70.051 0.172

[0106] Analyze the results of Tables 1-3 above:

[0107] From the results in Table 1, it can be seen that the Rockwell hardness of the flux-cored welding wires prepared in Examples 1-3 is between 60 and 62 HRC.

[0108] From the results in Table 2, it can be seen that the Vickers hardness of the flux-cored welding wires prepared in Examples 1-3 can still be maintained above 530 at a temperature of 850°C.

[0109] From the results in Table 3, it can be seen that the wear weight loss of the flux-cored welding wires prepared in Examples 1-3 is significantly lower than the wear weight loss of Cr26 high chromium cast iron, among which the wear weight loss of Cr26 high chromium cast iron is 2.3 times the wear weight loss of the flux-cored welding wire prepared in Example 2 (multiple = wear weight loss of Cr26 high chromium cast iron ÷ wear weight loss of the flux-cored welding wire in Example 2).

[0110] Example 6

[0111] High temperature and corrosion resistance test

[0112] The flux-cored welding wires prepared in Examples 1-3 and commercially available OCr25Ni2O heat-resistant stainless steel were used as samples to test the high temperature corrosion resistance through a molten salt corrosion test. The specific test steps were as follows: ① The sample surface was polished with 1200# sandpaper and placed in a crucible with a diameter of 50 mm; ② 40g of potassium nitrate + sodium chloride (mixed in a mass ratio of 1:1) was placed in the crucible; ③ The crucible was placed in a muffle furnace and kept warm at 750°C for 48 hours; ④ The surface of each sample was taken out and cleaned with pure water ultrasonic wave and then the surface corrosion was observed. The test results are shown in Table 4:

[0113] Table 4 High temperature and corrosion resistance test results

[0114]

[0115]

[0116] It can be seen from the results in Table 4 that, under the same test conditions, the molten salt corrosion resistance of the flux-cored welding wires of Examples 1-3 is better than that of the OCr25Ni2O heat-resistant stainless steel, and can better meet the needs of high temperature resistance and corrosion resistance.

[0117] The above is only an implementation method of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A high-hardness, crack-free flux-cored welding wire, comprising an outer sheath and a flux core filled in the outer sheath, characterized in that: The drug core comprises the following components by weight: Boron carbide 5.6-8.6 parts; 75% ferrosilicon 3.1-4.6 parts; electrolytic manganese 0.6-1.6 parts; 80% ferrovanadium 0.3-1.2 parts; nickel powder 0.3-1.0 parts; 68% high carbon ferrochrome 67.5-94.5 parts; iron powder 6-6.5 parts; Wherein, the filling rate of the medicine powder in the medicine core is 30-45%.

2. The high-hardness crack-free flux-cored welding wire according to claim 1, characterized in that: The drug core comprises the following components by weight: 7.1 parts of boron carbide; 3.7 parts of 75% ferrosilicon; 1.0 parts of electrolytic manganese; 0.6 parts of 80% ferrovanadium; 0.5 parts of nickel powder; 81 parts of 68% high carbon ferrochrome; and 6.2 parts of iron powder.

3. The high-hardness crack-free flux-cored welding wire according to claim 1, characterized in that: The filling rate of the medicine powder in the medicine core is 45%.

4. The high-hardness crack-free flux-cored welding wire according to claim 1, characterized in that: The chemical composition of the deposited metal of the flux core includes the following components by weight percentage: Boron: 1.8-2.8%; Carbon: 1.5-2.5%; Silicon: 1-1.5%; Manganese: 0.3-0.8%; Vanadium: 0.1-0.4%; Nickel: 0.1-0.4%; Chromium: 20-28%, the balance is iron.

5. A method for preparing a high-hardness crack-free flux-cored welding wire according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1, boron carbide, 75% ferrosilicon, electrolytic manganese, 80% ferrovanadium, nickel powder, 68% high carbon ferrochrome and iron powder are added to a dryer at a temperature of 180-220°C for 2-3 hours, and then put into a three-dimensional motion mixer at a temperature of 200°C to mix well, and then put into an incubator at a temperature of 140-160°C to keep warm, and the obtained core powder is set aside; S2, placing the outer skin on a forming machine, and rolling the outer skin steel strip into a U-shaped groove by the forming machine; S3, adding the flux core powder into the U-shaped groove and controlling the powder filling rate in the flux core to be 30-45%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and pulling it to obtain flux cored welding wire.

6. The method for preparing a high-hardness crack-free flux-cored welding wire according to claim 5, characterized in that: The temperature of the drying machine is 200°C, and the temperature of the heat preservation box is 150°C.

7. The method for preparing a high-hardness crack-free flux-cored welding wire according to claim 5, characterized in that: The outer skin is a low carbon steel strip.

8. The method for preparing a high-hardness crack-free flux-cored welding wire according to claim 7, characterized in that: The low carbon steel strip has a thickness of 0.4 mm and a width of 14 mm.

9. The method for preparing a high-hardness crack-free flux-cored welding wire according to claim 5, characterized in that: In S3, the welding wire is wiped with anhydrous ethanol before drawing.

10. The method for preparing a high-hardness crack-free flux-cored welding wire according to claim 8, characterized in that: The diameter of the flux-cored welding wire obtained by drawing is 2.8 mm.

Citation Information

Patent Citations

  • Flux-cored wire used for low-alloy ultrahigh-strength steel and manufacturing method thereof

    CN104741825A

  • High-tenacity high-hardness flux-cored wire

    CN106141505A

  • Steel mating welding rod for steam-temperature-ultra-supercritical thermal power generating unit and preparation method for steel mating welding rod

    CN106425158A

  • High-hardness self-protection overlaying flux-cored wire and preparation method thereof

    CN107052621A

  • Flux-cored wire for welding of titanium-steel dissimilar metal sheet and preparation method of flux-cored wire

    CN107378305A

Cited By

  • High-chromium cast iron surfacing flux-cored wire for shield tunneling machine and preparation method of high-chromium cast iron surfacing flux-cored wire

    CN121447320A